Conversion of methane using Mo-Mfi zeolite catalyst - Saidina Amin, Nor Aishah; Ngadi, Norzita; Prasetyoko, Didik (Penerbit UTM Press, 2003)
HZSM-5 (Si/Al = 30), silicalite and Mo-MFI with different molybdenum concentrations were synthesized by direct synthesis method. The catalyst samples were characterized using X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy and Temperature Programmed Desorption of Ammonia (TPD-NH3) techniques. The catalytic performance of the samples was evaluated in a continuous micro packed- bed reactor. The effects of metal content on methane conversion and products selectivity were investigated. Characterization results revealed that the samples were MFI-zeolite catalysts and the molybdenum metal most probably occluded in the defect sites of the zeolite. Modification of zeolite with metal resulted in the enhancement of catalytic activation. The experimental results using Mo(0.1)-MFI demonstrated a high selectivity of C1-oxygenates. However, Mo-MFI catalyst was found not suitable for gasoline production.